ANALISIS KESULITAN BELAJAR SISWA KELAS II PADA MATERI PENGURANGAN BILANGAN - Cindy Desiana; Hepsi Nindiasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the difficulties experienced by grade II students in solving subtraction problems and provide alternative solutions. The research approach used is a qualitative approach. The subjects of this study were grade II students in the first semester of Nurul Hidayah Integrated Science Elementary School, Sumur Pecung Subdistrict, Serang City, Banten Province. The key informant in this study was the grade II teacher, while the next informants were grade II students who were taken based on the key informant's suggestion and the Midterm Exam I scores which were then classified into high, medium, and low academic criteria. The data collection techniques used were written tests, interviews, and documentation, while to test the validity of the data, triangulation techniques were used. Based on the results of the study, it is concluded that the form of student learning difficulties in number reduction material includes misconceptions in operations involving zero numbers, not mastering number reduction by borrowing; difficulty interpreting story problems; and lack of accuracy in working on problems. Solutions offered to anticipate student learning difficulties during the learning process include applying learning based on the principles of mathematics learning, providing constructive practice questions, and providing reinforcement for concepts that students have not understood. Meanwhile, solutions to overcome student learning difficulties after Keyword : Learning Difficulties, Subtraction of Numbers.